Analysis of the Effect of Temperature Inhibitors on Corrosion Rate and Surface Structure Changes in Metal 2024-T3 - Nasruddin, Ibnu; Suyatmo, Suyatmo; Winiasri, Linda (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In seaplane design, the float is a component used for take off and landing in water that allows corrosion, in seaplane 172 skyhawk the float material is made of Aluminum 2024-T3. Corrosion is an event that changes the shape of the chemical structure of the metal which is a problem in the aviation industry because it can reduce the strength of the aluminum. The method used is weight loss according to ASTM G31-72 with inhibitor temperatures of 24℃, 28℃, and 32℃ with treatment without rinsing and rinsing every 120 hours, 240 hours, 360 hours, 480 hours and with seawater media that has a NaCl content of 3.5%. The results of this study obtained the corrosion rate of aluminum without rinsing at 24 ℃ has a corrosion rate of 2.294 mpy, while at 28 ℃ has a corrosion rate of 2.753 mpy, and at 32 ℃ has a corrosion rate of 3.212 mpy. Aluminum with rinsing at 24 ℃ has a corrosion rate of 1.376 mpy, while at 28 ℃ it has a corrosion rate of 1.835 mpy, and at 32 ℃ it has a corrosion rate of 2.294 mpy. The rinsing process reduced the corrosion rate by 66%. In seaplane maintenance with an average seawater temperature of 28 ℃ such as in the Banyuwangi sea, it is better to wash the seaplane float that has been submerged in the sea for a maximum of 120 hours once so that the corrosion rate does not increase, because based on the results of the study that Aluminum placed at 28 ℃ with treatment rinsed every 120 hours did not increase the corrosion rate.